Gestão e liderança na percepção de enfermeiros: um caminhar à luz da burocracia profissional. - Reis da Silva, Gilberto Tadeu; Galhardo Varanda, Patrícia Alves; Carneiro dos Santos, Nívia Vanessa; Batista da Silva, Naomy Safira; Silva Salles, Rilary; Coelho Amestoy, Simone; da Silva Teixeira, Giselle Alves; Pina Queirós, Paulo Joaquim (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2022)
Objective: to analyze the styles and factors involved in nurses’ management and leadership in three countries, Brazil, Portugal and Spain, in the light of Professional Bureaucracy. Method: a descriptive and exploratory study with a qualitative approach carried out in three university hospitals located in different countries, namely: Brazil, Spain and Portugal. Thirty nurses participated in the research. Data was collected through a collection script with sociodemographic questions and interviews analyzed using the WebQda software. Results: different perceptions about the integrating elements of participation in the three countries were revealed, highlighting communication from different perspectives. Some convergences in relation to teamwork were verified, where trust was the element that drives and motivates the team. It is a participatory relationship in the development of work. Conclusion and implications for the practice: in the three countries, it was possible to identify the importance of communication in the management process, as well as the management and leadership styles, as elements that favor performance of the team. Presence of relevant intervening factors was also evidenced, such as choice, organizational climate, interpersonal relationships, transparency in work and delegation of functions, which involves professional bureaucracy in which the nurses’ knowledge allows them to exercise their skills in a horizontal and participatory manner.